The leveraging of interfirm relationships as a distinctive organizational capability: a longitudinal study - Lorenzoni, Gianni; Lipparini, Andrea (Strategic Management Journal, 1999)
In this paper we present a study of the structure of three lead firm-network relationships at two points in time. Using data on companies in the packaging machine industry, we study the process of vertical disintegration and focus on the ability to coordinate competencies and combine knowledge across corporate boundaries. We argue that the capability to interact with other companies—which we call relational capability—accelerates the lead firm’s knowledge access and transfer with relevant effects on company growth and innovativeness. This study provides evidence that interfirm networks can be shaped and deliberately designed: over time managers develop a specialized supplier network and build a narrower and more competitive set of core competencies. The ability to integrate knowledge residing both inside and outside the firm’s boundaries emerges as a distinctive organizational capability. Our main goal is to contribute to the current discussion of cooperative ties and dynamic aspects of interfirm networks, adding new dimensions to resource-based and knowledge-based interpretations of company performance. Copyright © 1999 John Wiley & Sons, Ltd.